A Prestressing Strategy Enabled Synergistic Energy‐Dissipation in Impact‐Resistant Nacre‐Like Structures. Issue 6 (12th January 2022) - Wu, Kaijin; Song, Yonghui; Zhang, Xiao; Zhang, Shuaishuai; Zheng, Zhijun; Gong, Xinglong; He, Linghui; Yao, Hong‐Bin; Ni, Yong
Abstract: The application of prestresses is a valuable strategy for enhancing the overall mechanical performances of structural materials. Residual stresses, acting as prestresses, exist naturally in biological structural materials, such as the nacre with the 3D "brick‐and‐mortar" arrangement. Although regulation of the tablets sliding has recently been demonstrated to be vital to improve toughness in synthetic nacre‐like structures, the effects of prestresses on the tablets‐sliding mechanism in these nacre‐like structures remain unclear. Here, by a combination of simulation, additive manufacturing, and drop tower testing the authors reveal that, at a critical prestress, synergistic effects between the prestress‐enhanced tablets sliding and prestress‐weakened structural integrality result in optimized impact resistance of nacre‐like structures. Furthermore, the prestressing strategy is easily implemented to a designed nacre‐inspired separator to enhance the impact resistance of lithium batteries. The findings demonstrate that the prestressing strategy combined with bioinspired architectures can be exploited for enhancing the impact resistance of engineering structural materials and energy storage devices. Abstract : A bioinspired prestressing strategy is proposed to play the tablet‐sliding mechanism in nacre‐like structures more effectively. Synergistic effects between the prestress‐enhanced tablets sliding and prestress‐weakened structural integrality result in an optimized impact resistance at a critical prestress. The prestressing strategy is successfully implemented into the designed nacre‐like separators to significantly improve the impact tolerance and electrochemical performances of lithium batteries.